2023
DOI: 10.31004/obsesi.v7i3.4156
|View full text |Cite
|
Sign up to set email alerts
|

Career Management in Building Teacher Professional Performance

Yanti Hasbian Setiawati,
Hasan Baharun,
Halimatus Sa'diyah
et al.

Abstract: Teacher professionalism plays an essential role in educational institutions. Therefore, appropriate management is needed to realize the teacher's professional performance as expected. This study aims to analyze career management in building the teacher's professional performance in early childhood education institutions. The research method used is a qualitative case study type. Case study qualitative research was chosen to answer and explain the phenomenon of career management that has been carried out by fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Because they are the ones who can influence and move other humans to work towards achieving goals. The leader's task is to identify, direct, and motivate employees so that they can perform well, which will ultimately improve employee work discipline (Setiyaningsih, 2020;Rahmi et al, 2020;Maryani et al, 2021;Setiawati et al, 2023). This is supported by the research results of Brahmannanda & Suwandana (2018), McCarter et al (2022), and Andrianto et al, 2023 who found that leadership influences work discipline.…”
Section: Introductionmentioning
confidence: 90%
“…Because they are the ones who can influence and move other humans to work towards achieving goals. The leader's task is to identify, direct, and motivate employees so that they can perform well, which will ultimately improve employee work discipline (Setiyaningsih, 2020;Rahmi et al, 2020;Maryani et al, 2021;Setiawati et al, 2023). This is supported by the research results of Brahmannanda & Suwandana (2018), McCarter et al (2022), and Andrianto et al, 2023 who found that leadership influences work discipline.…”
Section: Introductionmentioning
confidence: 90%
“…Management is a series of processes of organizing and utilizing existing resources in the organization through the cooperation of these resources to achieve organizational goals that have been set effectively and efficiently (Setiawati et al, 2023). Therefore, this article is a site of the above opinion by believing that the success rate of an Educational Institution is determined by the program implemented based on the level of accuracy of the stages of management implemented.…”
Section: Introductionmentioning
confidence: 99%